2020
DOI: 10.3390/su12156230
|View full text |Cite
|
Sign up to set email alerts
|

Transport Models of Ammonium Nitrogen in Wastewater from Rare Earth Smelteries by Reverse Osmosis Membranes

Abstract: Wastewater from rare earth smelteries contains large amounts of ammonium nitrogen (NH4+-N), which causes severe environmental problems. In this contribution, the desalination efficiency of reverse osmosis (RO) was investigated in the treatment of NH4Cl or NaCl solutions from 0.1 to 40 g/L under different operating pressures with a commercial RO membrane. Experimental results showed that when an operating pressure above 30 bar is applied to the 5 g/L NH4Cl solution, the permeate was found to meet the discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the development of novel energy-efficient and eco-friendly synthesis and separation methods for various compounds, as well as purification technologies, are becoming urgently needed [ 2 , 3 , 4 ]. Membrane technologies meet all the requirements of “sustainable processes” and are of great interest as an alternative to traditional separation methods due to their advantages: cost- and energy-effectiveness, ecological safety, waste-free, and the ease of application and automation [ 5 , 6 , 7 , 8 ]. Pervaporation is one of the most promising membrane methods for the separation of the liquid mixtures of low molecular weight substances, especially for the thermally unstable and close-boiling compounds, azeotropic and isomeric mixtures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of novel energy-efficient and eco-friendly synthesis and separation methods for various compounds, as well as purification technologies, are becoming urgently needed [ 2 , 3 , 4 ]. Membrane technologies meet all the requirements of “sustainable processes” and are of great interest as an alternative to traditional separation methods due to their advantages: cost- and energy-effectiveness, ecological safety, waste-free, and the ease of application and automation [ 5 , 6 , 7 , 8 ]. Pervaporation is one of the most promising membrane methods for the separation of the liquid mixtures of low molecular weight substances, especially for the thermally unstable and close-boiling compounds, azeotropic and isomeric mixtures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grossi et al [ 144 ] showed that the UF-RO pilot-scale treatment of a gold mining effluent from the blasting stage can recover up to 80% nitrogen compounds at 6 bar. However, according to Gui et al [ 146 ] NH 4 Cl recovery by RO using a single module requires an operating pressure above 30 bar if the solution contains 5 g/L NH 4 Cl, and the concentration of ammonium must be reduced to the discharge standards. Therefore, a series of multiple NF and RO modules are needed to concentrate nutrients to commercially viable concentrations [ 20 ], which adds complexity of process control.…”
Section: Modern Trends In Nutrients Recoverymentioning
confidence: 99%
“…Therefore, the question of more effective separation of BaCl2 aqueous solution is still actual. It is well known that pressure driven membrane processes, including reverse osmosis, are highly effective for the separation of diluted salt solution in water [20,21]. However, the question of applying such processes for Barium Chloride is not described in the literature with satisfying fullness.…”
Section: Introductionmentioning
confidence: 99%